Chromatographic and Spectral Analysis of Two Main Extractable Compounds Present in Aqueous Extracts of Laminated Aluminum Foil Used for Protecting LDPE-Filled Drug Vials - Samuel O. Akapo; Sajid Syed; Anicia Mamangun; Wayne Skinner (International Journal of Analytical Chemistry)
Laminated aluminum foils are increasingly being used to protect drug products packaged in semipermeable containers (e.g., low-density polyethylene (LDPE)) from degradation and/or evaporation. The direct contact of such materials with primary packaging containers may potentially lead to adulteration of the drug product by extractable or leachable compounds present in the closure system. In this paper, we described a simple and reliable HPLC method for analysis of an aqueous extract of laminated aluminum foil overwrap used for packaging LDPE vials filled with aqueous pharmaceutical formulations. By means of combined HPLC-UV, GC/MS, LC/MS/MS, and NMR spectroscopy, the two major compounds detected in the aqueous extracts of the representative commercial overwraps were identified as cyclic oligomers with molecular weights of 452 and 472 and are possibly formed from poly-condensation of the adhesive components, namely, isophthalic acid, adipic acid, and diethylene glycol. Lower molecular weight compounds that might be associated with the “building blocks” of these compounds were not detected in the aqueous extracts.